NGHIÊN CỨU CHUYỂN HÓA ZERUMBONE OXIT VỚI MỘT SỐ AXIT HYDRAZID THƠM - Vương, Văn Trường; Phạm, Duy Nam; Trịnh, Thị Thùy Liên; Phạm, Thị Duyên; Nguyễn, Đăng Đạt (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON TRANSFORMATION OF ZERUMBONE OXIDE WITH AROMATIC HYDRAZIDEZerumbone was isolated from several plant species of the Zingiberaceae family which have many potential biological activities, such as antiproliferative, antioxidant, anti-inflammatory, and anticancer activities. Due to these biological effects, many scientists have managed to synthesize zerumbone derivatives and evalute their bioactivities. In this paper, we report some results in the synthesis of six new zerumbone derivatives by the condensation of zerumbone oxide with aromatic hydrazides. The structures of these compounds have been confirmed by 1H NMR, 13C NMR and ESI-MS spectroscopic data.